Effect Of Progressive Muscle Relaxation On Anxiety - Erindra Budi Cahyanto; Kanthi Suratih (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
Background : Teenagers need support to get through the musical period, let alone living with their parents. In the conditions of the COVID-19 pandemic, the stressors experienced are even greater. Adolescents need non-pharmacological support to stay healthy. This study aims to determine the effect of progressive muscle relaxation on adolescent anxiety in orphanages.Subjects and Methods: This type of research is quasi-experimental. This research was conducted at the Mardhatillah Sukoharjo Orphanage, Central Java. The subjects were 42 people, divided into the control group (27 people) and the intervention group (15 people). Measurements were made before and before the intervention. The intervention group received the usual treatment plus progressive muscle relaxation for 4 weeks, while the control group was given the usual treatment. The measuring instrument uses HARS. Data were analyzed by paired t test not using the SPSS 21 program.Results: There was a significant difference between the treatment and control groups with a mean of 7.80 and 10.48 (p < 0.001).Conclusion: Advanced muscle relaxation can reduce the anxiety of adolescents living in the Mardhatillah orphanage, Sukoharjo, Central Java.Keywords: Progressive muscle relaxation; teenager; orphanage, anxiety